Evaluation of association of DRD2 TaqIA and -141C InsDel polymorphisms with food intake and anthropometric data in children at the first stages of development - Feistauer, Vanessa (Genet Mol Biol, 2018)
The reward sensation after food intake may be different between individuals and variants in genes related to the dopaminergic system may indicate a different response in people exposed to the same environmental factors. This study investigated the association of TaqIA (rs1800497) and -141C InsDel (rs1799732) variants in DRD2/ANKK1 gene with food intake and adiposity parameters in a cohort of children. The sample consisted of 270 children followed until 7 to 8 years old. DNA was extracted from blood and polymorphisms were detected by PCR-RFLP analysis. Food intake and nutritional status were compared among individuals with different SNP genotypes. Children carrying the A1 allele (TaqIA) had higher energy of lipid dense foods (LDF) when compared with A2/A2 homozygous children at 7 to 8 years old (GLM p=0.004; Mann Whitney p=0.005). No association was detected with -141C Ins/Del polymorphism. To our knowledge, this is the first association study of the DRD2 TaqIA and -141C Ins/Del polymorphism with food intake and anthropometric parameters in children. DRD2 TaqIA polymorphism has been associated with a reduction in D(2) dopamine receptor availability. Therefore, the differences observed in LDF intake in our sample may occur as an effort to compensate the hypodopaminergic functioning.